Anthobium frigidum Shavrin 2022, comb.nov. - Shavrin, Alexey V. (Zenodo, 2022)
Anthobium frigidum (J. Sahlberg, 1880) comb.nov. (Figs. 67–68, 82–86) Deliphrum frigidum J. Sahlberg, 1880: 108; Luze 1905: 245 Type material examined: Syntypes: 1 ♂: ‘Sibir arct’, ‘J. Sahlb. | ind. typ’, ‘Sibirie Jénissée’, ‘frigidum | J. Sahlb.’, ‘R.I.Sc.N.N. 17.479 | Deliphrum | Coll. et det. A. Fauvel’, ‘Syntype’, ‘ Anthobium | frigidum (J. Sahlberg, 1880) | Shavrin A.V. det. 2021’ (Fig. 63; IRSN); 3 ♂♂, 4 ♀♀: ‘Tolstoinos’ , ‘J. Sahlb. | ind. typ’ , ‘Coll. et det A. Fauvel | Deliphrum [handwritten] | frigidum J.Sahlb. [handwritten] | R.I.Sc.N.B. 17.479’ , ‘Syntype’ , ‘ Anthobium | frigidum (J. Sahlberg, 1880) | Shavrin A.V. det. 2021’ (IRSN); 3 ♂♂: 2 ♀♀: ‘Tolstoinos 70°10’’ , ‘Sibir Jeniseie’ , ‘ frigidum J. Sahlb. ’ <handwritten>, ‘J. Sahlb. ind. typ’ , ‘2319’ (SMNH). Additional material examined: RUSSIA: TYUMEN AREA: 1 ♂, 1 ♀: Uvatskiy District, 10 km S Gornoslinkino, near Tobolsk Field Research Station of Severtsov Institute. Mosses and litter in forests with Abies , Picea , Betula , Carex globularis , Calamagrostis sp., Equisetum sylvaticum , Pyrola sp., Maianthemum bifolium , Linnaea borealis , Oxalis acetosella , Solidago sp., Lathyrus sp., Lonicera sp., Hylocomium splendens , Pleurozium schreberi , Dicranum polysetum etc. 13.09.2003. A.B. Ryvkin leg. (ZMM); KHANTY- MANSI AUTONOMOUS REGION: 2 ♂♂, 1 ♀: Surgutskiy District, Yuganskiy Nature Reserve, Vachempeu River (right confluent of Bolshoy Yugan River), 3 km SW of Kamenniy codon. Steep loamy bank of river: Carex spp., grasses, sporadic Filipendula ulmaria , Vicia sp., Veronica ? longifolia etc. 21.08.1999. A.B. Ryvkin leg. (cSh, ZMM); 2 ♂♂, 1 ♀: same data, Malyi Yugan River, 3 km up-stream Vuya-Yany River. In geophilous and epigenous fungi and litter among those in flood-plain birch forest with Maianthemum , young Picea and Abies , Rosa sp. etc. 14.08.1998 (cSh); 1 ♀: same data, basin of Kol-Kochen-Yagun River (confluence of Malyi Yugan River), lake near cordon. Mosses and litter under Pinus sylvestris , P. sibirica and Abies in forest at ridge ...